Digital Eye Strain During COVID-19 Lockdown in Jeddah, Saudi Arabia - Almarzouki, Nawaf; Faisal, Konooz; Nassief, Arwa; Najem, Noura; Eid, Rayana; Albakri, Renad; Alhibshi, Dana; Alwethinani, Shehana; Ashi, Heba (Journal of Contemporary Medical Sciences, 2021)
Objectives: This study aimed to determine the prevalence of computer vision syndrome (CVS) and associated risk factors of prolonged use of electronics. Methods: This was an online non-interventional cross-sectional studyconducted over the period of COVID curfew in Jeddah city from April to June 2020, through a questionnaire. Participants were between 20 and 60 years of age and used electronic devices. Results: Total 1,227 participants were recruited between 20 and 60 years of age. The majority of them were females (69.9%). Almost 1,048 participants used smartphones or laptops. More than half (54.5%) of them used electronics for more than 4 hours daily. A high symptom severity score was found in 44% of the respondents. Taking breaks during electronics use <30 minutes (P=0.018), viewing computers at a distance less than arm length (P=0.001), and the use of screen protectors (p=0.014) were significant factors related to the symptom’s severity score. Conclusion: CVS was prevalent among the participants who used electronics for more than 4 hours daily. Taking breaks during electronics use, viewing computers at an appropriate distance, and the use of screen protectors were effective practices to relieve the eye symptoms severity score.